Evidence-based treatment of multicystic dysplastic kidney: a systematic review. Issue 6 (December 2018) - Chang, A.; Sivananthan, D.; Nataraja, R.M.; Johnstone, L.; Webb, N.; Lopez, P.-J.
Summary: Objectives: There is a lack of a standardised protocol for the investigation and non-operative management of paediatric multicystic dysplastic kidney (MCDK). Institutional protocols for non-operative management remain essentially ad hoc. The primary outcome of this systematic review is to establish the incidence of hypertension associated with an MCDK. The secondary outcome is to determine the malignancy risk associated with an MCDK. The tertiary outcome is to assess the rate of MCDK involution. Subsequent to these, an evidence-based algorithm for follow-up is described. Methodology: A systematic review of all relevant studies published between 1968 and April 2017 was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies were identified by specific inclusion and exclusion criteria, all of which included data relevant to the primary, secondary and tertiary outcomes. Hypertension was defined as systolic blood pressure greater than the 95th centile for gender, age and height centile. Subset analysis was performed for hypertension associated with an MCDK. Results: The primary outcome measure revealed a 3.2% (27/838) risk of developing hypertension associated with an MCDK. The secondary outcome measure noted a 0.07% malignancy risk (2/2820). The tertiary outcome measure established that 53.3% (1502/2820) had evidence of involution of the dysplastic kidney. A total of 44 cohort studies (2820 patients) were analysed. Conclusion: Given the low risk of hypertension and malignancy, which is similar to the general population, the current conservative non-operative pathway is an appropriate management strategy. An algorithm to help support clinicians with ongoing management is proposed.